Phytochemical Study, Polyphenols Determination and Evaluation of Antioxidant Activity of Satureja calamintha from Morocco - Halmoune, Asma; Salhi, Nadia; Hamza, EL Finou; Abdessamad, Ait Benlabchir; Khalid, Khfif; Abdelhamid, Zaid; Ihoussaine, El Rhaffari (Indian Journal of Pharmaceutical Education and Research, 2024)
Introduction The domestication of Satureja calamintha, either because of its superior tolerance to disease and environmental factors or because of its potential for larger quantities of useful chemicals. Materials and Methods wild plants were harvested in the Ksar El Kabîr region, Morocco, and seeds were planted in open-air plots. Part of the cultivated plant was then harvested after one year of planting, while the other was harvested after two years. Results The results show that the plant cultivated and harvested in the second year is characterized by a slightly higher polyphenol content for all three extraction methods than the same plant cultivated in the first year, and that the spontaneous plant, particularly the decoction, has the highest content (174.42±0.52 mg GAE/g extract), while the infused extract has the lowest content (123.242±5.64 mg GAE/g extract). Decoction and infusion remain suitable extraction extraction methods for total flavonoids for the plant grown in the second year, representing (86.23±0.12 mg EQ/g extract) and (76.45±0.06 mg EQ/g extract) respectively, followed by macerate of the spontaneous plant (57.7±1.46 mg EQ/g extract). In terms of antioxidant activity, the extract obtained by decoction and harvested in the second year showed high antioxidant activity against DPPH (IC50=1.174±0.141mg/mL), FRAP(EC50=4.254±0.03) and ABTS (IC50=9.969±0.09 mg/mL), while maceration showed low activity against the same three tests. Conclusion The aqueous extracts of the studied spontaneous and cultivated plants showed positive results for all activities and were characterized by an increase in phytochemicals, particularly in the extracts from the second year.
Keywords: Satureja calamintha (L); Wild plant; Cultivated plant; Flavonoids; Polyphenols; Antioxidant potential